2017
DOI: 10.18632/oncotarget.15752
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between ΔNp63 and miR-138-5p regulates growth, metastasis and stemness of oral squamous cell carcinoma

Abstract: TP63 acts as a master regulator in epithelia development and in the progression of various cancers, but its role in oral cancer pathogenesis remains unknown. This study aimed to explore the role of TP63 in the progression of oral squamous cell carcinoma (OSCC). This study shows that ΔNp63, the predominant isoform of TP63, is significantly upregulated in OSCC tissues and cell lines compared with their normal counterparts, and its expression is closely correlated with pathological differentiation, lymph node met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 58 publications
(72 reference statements)
3
26
0
Order By: Relevance
“…Both diabetes mellitus and HPV infection were reported as risk factors that enhanced the metastatic potential and predict poor prognosis in TSCC. The dysregulation of ΔNp63, PTEN, ATK1 and miRNAs, etc. was involved in the prognosis of TSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Both diabetes mellitus and HPV infection were reported as risk factors that enhanced the metastatic potential and predict poor prognosis in TSCC. The dysregulation of ΔNp63, PTEN, ATK1 and miRNAs, etc. was involved in the prognosis of TSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer stem cells (CSCs) are known to play a key role in tumor initiation and disease relapse due to the properties of self‐renewal and drug resistance . Expression of CSC markers ( NANOG, OCT4 , and SOX2 ) has been correlated with oral cancer progression/tumorigenesis . Multiple studies, including from our group, have shown correlation between expression of NOTCH1, CD133, ALDH1A1, CD44 , and chemotherapy resistance, recurrence/prognosis .…”
Section: Introductionmentioning
confidence: 86%
“…[7][8][9] Expression of CSC markers (NANOG, OCT4, and SOX2) has been correlated with oral cancer progression/ tumorigenesis. 10,11 Multiple studies, including from our group, have shown correlation between expression of NOTCH1, CD133, ALDH1A1, CD44, and chemotherapy resistance, recurrence/prognosis. 12 Further studies have correlated expression of CSC (CD44, ALDH1A1, NOTCH1) and Epithelial Mesenchymal Transition (EMT) (CADHERIN, TWIST, TGF-βeta, MMPs) markers with the process of invasion and metastasis.…”
Section: Introductionmentioning
confidence: 95%
“…1 Gressner et al found that endogenous TAp63 is induced by many chemotherapeutic agents like Bleomycin, Doxorubicin and Mitroxantrone in Hepatocellular carcinoma cell lines. 15 Also, ΔNp63 expression is directly correlated with the clinical response to cisplatin in patients with HNSCC. 16 There is a downregulation of ΔNp63 and upregulation of TAp63 levels after DNA damage.…”
Section: Therapeutic Considerationsmentioning
confidence: 99%
“…Both p63 (ΔNp63) and p73 are critical mediators of cell death following chemotherapy in HNSCC. 15 In HNSCC, after cisplatin treatment, ΔNp63 is phosphorylated, exported from the nucleus into the cytoplasm and targeted by RACK 1 for proteasome degradation.Thus, in HNSCC, patients with high levels of ΔNp63 are associated with a good response to platinum-based chemotherapy. 5 There is a similar mechanism regulating tumor cisplatin sensitivity in triple negative breast cancer.…”
Section: Therapeutic Considerationsmentioning
confidence: 99%